2019
DOI: 10.1002/slct.201902742
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Biological Importance of Herboxidiene/GEX1A

Abstract: The importance of exceptionally potent bioactivities, scarcity of natural abundance and interesting structural features of herboxidiene/GEX1A attracted great interest from synthetic, medicinal chemists. In this review we discussed chemical syntheses and biological significances of herboxidiene/GEX1A. Aim of this review to gather valuable insights by various research groups into one place, to accelerate and design an efficient synthetic methods and surplus biological studies of herboxidiene/GEX1A. Existing repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Showdomycin is a uridine analog and has been shown to have antibacterial [ 65 ] along with antitumor activity [ 66 , 67 ]. Herboxidiene, found in both strains, is a wide-range metabolite that targets mRNA splicing [ 68 ]. WS9326 is NRPS with a rare N-terminal cinnamoyl moiety and has been shown to exhibit anti- Candida activity by the inhibition of isocitrate lyase [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Showdomycin is a uridine analog and has been shown to have antibacterial [ 65 ] along with antitumor activity [ 66 , 67 ]. Herboxidiene, found in both strains, is a wide-range metabolite that targets mRNA splicing [ 68 ]. WS9326 is NRPS with a rare N-terminal cinnamoyl moiety and has been shown to exhibit anti- Candida activity by the inhibition of isocitrate lyase [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…[161] and serves as a splicing inhibitor that specifically impairs the SF3B function by binding to SF3B1 [162]. Studies involved in the search for synthetic analogues of GEX1A revealed that the splicing inhibitory potency of the analogues and the modification of carboxylic acid moiety are well correlated with the antiproliferative activity against cancer cell lines [163,164].…”
Section: Representative Sf3b1 Inhibitors and Isoginkgetinmentioning
confidence: 99%
“…Most splicing modulators reported to date are naturally occurring molecules, including the FR class [ 12 , 13 , 14 , 15 ], herboxidiene class [ 16 , 17 ], and pladienolide class ( Figure 1 ). Among them, pladienolides are structurally unique in that they possess a highly substituted macrocyclic core structure that has captured the attention of the synthetic chemistry community.…”
Section: Introductionmentioning
confidence: 99%